The Role of Mycophenolate Mofetil for the Induction of Remission in ANCA-Associated Vasculitis: A Meta-Analysis - Xiong, Anji; Xiong, Chen; Yang, Guancui; Shuai, Yu; Liu, Deng; He, Linqian; Guo, Zepeng; Zhang, Liangwen; Liu, Yi; Yang, Yuan; Cui, Beibei; Shuai, Shiquan (Frontiers in Medicine, 2021)
Objectives: The successful introduction of mycophenolate mofetil (MMF) as a treatment for renal allograft reduced the incidence of acute rejection. The inspiring effects obtained by the MMF have led to an evaluation of its therapeutic potency on ANCA-associated vasculitis (AAV). However, there is little evidence of the MMF's efficacy on the AAV. The meta-analysis is carried out to evaluate the efficacy of MMF as a remission induction therapy in AAV. Methods: Up to June 30th, 2020, PubMed, Cochrane Library and Embase have been searched comprehensively. According to heterogeneity, the pooled remission rates are synthesized by either fixed-effect or random-effect models. Results: The eight included studies comprising two hundred and thirty patients who were treated with MMF as induction therapy are included in our analysis. The pooled overall remission rate is 74% (95% CI: 0.68–0.80). The remission rate, the infection rate and the rate of leukopenia of four randomized controlled trials aimed at comparing the effects of MMF with cyclophosphamide (CYC) during induction therapy for AAV have no statistical significance (P>0.05). Conclusion: MMF may be an alternative to CYC for remission induction therapy in AAV with MPO-ANCA, mild to moderate renal involvement and non-life-threatening state. Whether to observe the effect of MMF in AAV or to compare the difference between MMF and CYC in the future studies, risk stratification and subgrouping of AAV patients should be first carried out to correctly identify the AAV subgroup suitable for MMF.